Some Theoretical and Practical Issues of Medical Geographical Research (Indian Journal of Forensic Medicine & Toxicology, 2020)
In the context of globalization of global economy and intense competition and steady increase inpopulation, mortality rates among people with infectious and parasitic diseases are increasing. Internationalorganizations are also paying much attention to fighting these problems and their consequences. In particular,the UN Sustainable Development Program up to 2030 emphasizes “issues related to the elimination ofimmunodeficiency, tuberculosis and malaria epidemics in the period up to 2030, as well as measures to combathepatitis and other waterborne infections”. Successful implementation of these tasks requires stabilizationof nosocheological and nosogeographic situations in arid climates. Medical geographical situation in theregions is one of the most important factors determining the development of society and the way of life ofthe population. Addressing medical geographical problems and improving public health, reducing morbidityand increasing life expectancy are of vital scientific and practical importance.